Creating Mexican Consumer Culture in the Age of Porfirio Díaz - Bunker, Steven B., 1970- (Book collections on Project MUSE., 2012)
"This study shows how goods and consumption embodied modernity in the time of Porfirio Díaz. Through case studies of tobacco marketing, department stores, advertising, shoplifting, and a famous jewelry robbery and homicide, he provides a tour of daily life in Porfirian Mexico City, overturning conventional wisdom that only the middle and upper classes participated in this culture"--Provided by publisher.